Influence of Challenge-Based Learning (CBL) Incorporating Pulo Gold-craft Ethnoscience to Improve Science Students' Creative Thinking Skills - Ahmad, Nur; Laela, Rizka Amalia; Ridlo, Zainur Rasyid; Amrullah, Jadnika Dwi Rakhmawan; Putra, Pramudya Dwi Aristya (FKIP Universitas Lampung, 2025)
The Challenge-Based Learning (CBL) model synthesises problem-based, project-based, and contextual learning approaches into an integrative pedagogical framework. Ethnoscience connects indigenous knowledge systems with scientific inquiry and provides cultural relevance to science education. This study focuses on the gold and silver craftsmanship of Pulo Village in Tempeh Subdistrict—a generational practice rooted in local ethnoscientific traditions, where artisans employ empirically derived metallurgical techniques. By embedding these indigenous practices into CBL, the research investigates how ethnoscience-informed pedagogy enhances junior high school students' creative thinking skills in understanding temperature, heat, and thermal expansion. Quasi-experimental research followed a posttest-only control group design and was conducted using a purposive sampling technique in the 7th grade at SMPN 7 Tempeh, Lumajang, Indonesia. Primary data was a creative thinking skills posttest, while secondary data was interviews and documentation. Sample data were analysed using homogeneity and normality tests using Kolmogorov-Smirnov. The data proved normal, so the hypothesis test used the Independent Sample T-test. The results obtained showed that there was an effect of creative thinking on students with a two-sample t-test value of significance (2-tailed) (0.003 ≤ 0.05) and the right-tailed t-test, which obtained the value of tcount> ttable (3.097> 2.005). It was concluded that this study, with the application of the ethnoscience-based Challenge-Based Learning (CBL) approach, will influence the improvement of the creative thinking of junior high school students. In the CBL, the learners would collaboratively compose their ideas to solve problems and adjust some results to strengthen creative thinking skills aligned with culturally relevant real-world challenges. Keywords: challenge-based learning, ethnoscience, creative thinking skills.